2009
DOI: 10.1002/ijc.24956
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 and CXCR7 regulate angiogenesis and CT26.WT tumor growth independent from SDF‐1

Abstract: Recent studies have shown that the chemokine stromal cell-derived factor (SDF)-1 and its receptor CXCR4 are involved in the metastatic process of colorectal cancer. The impact of SDF-1 on the stimulated metastatic growth during hepatectomy-associated liver regeneration is unknown. With the use of a heterotopic murine colon cancer model, we analyzed whether blockade of SDF-1 inhibits angiogenesis and extrahepatic growth of colorectal cancer after liver resection. Functional neutralization of SDF-1 by 1 mg/kg bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 49 publications
0
52
1
Order By: Relevance
“…CXCR7 can be therapeutically targeted by non-peptidergic small molecules, siRNA as well as conventional antibodies (3,11,18). In the present study we identified a novel class of potential therapeutics targeting CXCR7, llama-derived immunoglobulin single variable domains (Nanobodies) specifically directed against CXCR7.…”
mentioning
confidence: 92%
“…CXCR7 can be therapeutically targeted by non-peptidergic small molecules, siRNA as well as conventional antibodies (3,11,18). In the present study we identified a novel class of potential therapeutics targeting CXCR7, llama-derived immunoglobulin single variable domains (Nanobodies) specifically directed against CXCR7.…”
mentioning
confidence: 92%
“…12 The majority of the reports drew the conclusion that CXCR7 serves as a positive regulator in enhancing proliferation/metastasis of tumors. [13][14][15][16] Similar to CXCR4, the function of CXCR7 in tumor cells is still controversial. It was revealed by Liberman et al 17 and Uto-Konomi et al 18 that CXCR7 acted as a negative regulator for CXCL12/ CXCR4 axis and elicited anti-tumorigenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, CXCR7 is expressed in embryonic and adult tissue as well as on tumor cells (10,12,13). Elevated levels of CXCR7 were observed in aggressive colon (14) and colorectal cancer brain metastases (15).…”
Section: Introductionmentioning
confidence: 99%